From national humiliation to difference: The image of the Circassian beauty in the discourses of Circassian diaspora nationalists - Dogan, Setenay Nil (HOMER ACADEMIC PUBL HOUSE, 2010)
The Circassian Beauty, attributed to the women of the Caucasus, is a historical image of idealized feminine aesthetics that has prevailed in Orientalist literature, art and knowledge production as well as Turkish popular culture. This article argues that this image has been central to the gendered construction of diasporic identity among Circassian diaspora nationalists in Turkey. It aims to explore the multiple meanings attached to the image of the Circassian Beauty, and the ways in which these meanings are historically transformed in line with the political and historical transformations of the Circassian diaspora in Turkey.
Keywords: Diaspora nationalism; gender; Circassians; Circassian Beauty; Turkey; Area Studies; Social Sciences - Other Topics